Comparison of Solute Clearance, Hospitalization Rate, and Aortic Arch Calcification between Online Hemodiafiltration and High-Flux Hemodialysis: A 6-Year Observational Study - Na Hao; Cheng-Hong Yang; Hong-Tao Yang; Chien-Hsing Wu; Yang-Yang Lei; Yu-Pin Wu; Wan-Ting Lin; Terry Ting-Yu Chiou; Jin-Bor Chen (Karger Publishers, 2019)
Background/Aims: Studies on the long-term clinical benefits of hemodiafiltration (HDF) and high-flux hemodialysis (HFHD) are very limited. This study aimed to investigate the hospitalization rate and aortic arch calcification (AAC) of these two dialysis modalities over 6 years. Methods: Participants who received regular HDF and HFHD in one hospital-facilitated hemodialysis center were prospectively enrolled after matching for age, sex, and diabetes between January 2009 and December 2014. Medical records were reviewed retrospectively on demographics, laboratory variables, calcified scores in aortic arch measured by chest radiography, and rates of hospital admission. Cox proportional hazard regression and linear regression were used to obtain the outcome results. Results: The HDF and HFHD groups consisted of 108 and 102 participants, respectively. Levels of laboratory variables including small soluble solutes and Kt/V were not statistically different over the 6-year period between the HDF and HFHD groups. Calcified scores of the aortic arch increased over 6 years in both groups. The changes in the mean calcified scores were significant when compared between the two groups (0.44-1.82 in HFHD, 0.79-1.8 in HDF, respectively, p = 0.008). Hospitalization rates were 735 per 1,000 patients in the HDF group and 852 per 1,000 patients in the HFHD group, respectively. No significant difference was observed in frequency and days of hospitalization between HDF and HFHD. Conclusion: Hospitalization rates and AAC were observed to be equal for HDF and HFHD.